Efficacy of Biotic and Chemical Inducers of SAR in Management of Plant Viruses - Dutta, Himashree; Kumar, R. Gowtham; Borah, Munmi (International Journal of Economic Plants, 2019)
The objective of this study was to review the published research works on management of viral diseases of crop plants in recent years using microbial antagonists and chemical inducers of SAR. Systemic acquired resistance (SAR) and induced systemic resistance (ISR) are two forms of induced resistance; in both SAR and ISR, plant defenses are preconditioned by prior infection or treatment that results in resistance (or tolerance) against subsequent challenge by a pathogen or parasite. Much of this knowledge is due to the identification of a number of chemical and biological elicitors, some of which are commercially available for use in conventional agriculture. The biocontrol potential of Bacillus spp. and Pseudomonas spp in relation with their antagonizing attributes against plant viruses revealed their efficacy against Tobacco Mosaic Virus (TMV), Cotton leaf curl virus (CLCuV), Cucumber mosaic virus (CMV) and some other plant viruses are discussed in this review. Recent researches on mechanisms of biological control by PGPR revealed that several plant growth promoting rhizobacteria (PGPR) strains protect plants against viral infection through induction of systemic resistance. Studies were done to evaluate specific strains of PGPR for induced resistance in indicator plants like Chenopodium and Arabidopsis thaliana. The classic form of SAR can be triggered by exposing plant to virulent, avirulent, and nonpathogenic microbes viz. microbial antagonist, or artificially with chemicals such as salicylic acid 2,6-dichloro-isonicotinic acid (INA) or benzo (1, 2, 3) thiadiazole-7-carbothioic acid S-methyl ester (BTH) etc. which are considered as chemical inducers of SAR. Progress with efficient use of different biological agents against plant viruses is a worthwhile approach in context of sustainable crop health management.